PENGEMBANGAN PANDUAN PRAKTIK KEPERAWATAN BERDASARKAN PEKA BUDAYA DAN FORMULIR ASESMEN KEPERAWATAN PASIEN MENJELANG AKHIR KEHIDUPAN - Sarma, Eva Winda; Novieastari, Enie; Pujasari, Hening (Poltekkes Kemenkes Bandung, 2025)
Culturally congruent care practices are essential for providing holistic and meaningful care, particularly for multicultural populations and the end-of-life patients. However, national policies have not been fully implemented within hospital internal policies. This study aimed to develop a culturally congruent care practices guideline and a nursing assessment form for the end-of-life patient. A case study employing the Eight-Step Kotter Change Model was used to develop, implement, and evaluate the guideline and form at Hospital X Jakarta. Socialization was conducted with ICU nursing staff and nurse managers. Nineteen out of forty-one study participants were purposively selected to participate in the evaluation. The results demonstrated that the development of the guideline and form successfully improved nurses’ knowledge related to culturally sensitive nursing, with 80% of the evaluation questions showing increased scores. Subsequently, the guideline and form were integrated into hospital policies and electronic medical records to ensure sustainability. A systematic approach using Kotter’s Model effectively facilitated the development of culturally congruent care practices. Leadership support and ongoing competency development are necessary to sustain these changes and enhance the quality of care.